Data mining in predicting firms failure: a comparative study using artificial neural networks and classification and regression tree / Norashikin Nasaruddin ...[et al.] - Nasaruddin, Norashikin; Che-Hussai; Nayan, Asmahani; Ahmad, Abd-Razak (2015)
Financial Institutions and investors alike are very much interested in the accuracy of predicting the potential failures of firms. These financial institutions believe accurate prediction will lead to a low default rate in servicing their financial loans. The aim of this study is to find a better model to classify firms that is more likely to fail. Bad prediction model will lead to a high default rate. Using financial and non-financial information, this paper illustrates the construction and comparison of two models - artificial neural networks (NN) and classification and regression tree (CART) models to classify the failed from the non-failed firms. This study found that based on the training sample's result (NN = 94.03% & CART = 94.69%) the overall accuracy result of CART is higher than the NN model. Similar result can be drawn for the validation sample with CART leading at 92.93% overall accuracy rate compared to NN's 91.92%.